QRIS Adoption as a Cashless Transaction: A Case Study of Meatball Seller in Makassar City - Andi Urfia Awaliah; Bachrudin K. Una; Cesilia Arum Septianingsih; Putri Ratnasari (Fakultas Ekonomi dan Bisnis Universitas Udayana, 2025)
The previously free QRIS adoption now incurs fee of 0.3% for small businesses and 0.7% for medium and large businesses, as determined by Bank Indonesia. This phenomenon has sparked debates and divided opinions among meatball traders in Makassar City. As a metropolitan city in Eastern Indonesia, Makassar is the city with the largest population of MSMEs compared to other cities in Eastern Indonesia. Despite the Trade Department’s efforts to promote QRIS, many meatball traders in Makassar city have not adopted it. This research aims to analyze the perceptions of meatball traders regarding their interest in implementing cashless through adopting QRIS as a potential for expanding sales and reducing manual errors in cash calculations. This qualitative research involved informants (16 buyers and 20 meatball sellers), in research data analysis techniques using the help of NVivo software. The research results found that QRIS adoption provides various conveniences, security and expands customer reach as well as increases efficiency in the cashless business transaction process.